Freshwater crabs of the Near East: Increased extinction risk from climate change and underrepresented within protected areas - Masoud Yousefi; Reza Naderloo; Alireza Keikhosravi (Global Ecology and Conservation, 2022)
Climate change is known as an important threat to biodiversity, particularly for freshwater organisms as they have limited dispersal ability. Freshwater crabs are ecologically important freshwater macro-invertebrates and play a key role in their ecosystem. In this study we used an ensemble approach using three machine learning methods (Generalised Boosted Models, Maximum Entropy modeling, Random Forest) and assessed the impacts of climate change on the distribution of eight freshwater crabs (Potamon elbursi, P. fluviatile, P. hippocratis, P. ibericum, P. pelops, P. persicum, P. potamios, P. strouhali) and estimated the protected area coverage for their suitable habitats under current and future climate predictions. We found that the suitable habitats of six species will decrease (P. elbursi, P. fluviatile, P. hippocratis, P. pelops, P. potamios and P. strouhali) while the other two species (P. ibericum and P. persicum) will gain new suitable habitats due to climate change. Loss of suitable habitat would be substantial for the P. hippocratis and P. elbursi as these species will lose 92 %–100 % and 75 %–100 % of their suitable habitats by 2070, respectively. Additionally, P. fluviatile and P. pelops will lose 70 %–95 % and 81 %–86 % of their current suitable habitat, respectively. Thus, they are particularly sensitive to climate change. We showed that a very small proportion (<1 %) of each species’ current suitable habitat is covered by protected areas ranging from zero in P. elbursi, P. persicum and P. strouhali to 0.96 % in P. fluviatile. Under both climate change models P. elbursi, P. hippocratis and P. potamios will not have protected habitat in the future. Suitable habitats identified to remain stable under climate change will play a critical role in conservation of these freshwater species and will act as climate change refugia.